The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pgen.1005049
|View full text |Cite
|
Sign up to set email alerts
|

Replicative DNA Polymerase δ but Not ε Proofreads Errors in Cis and in Trans

Abstract: It is now well established that in yeast, and likely most eukaryotic organisms, initial DNA replication of the leading strand is by DNA polymerase ε and of the lagging strand by DNA polymerase δ. However, the role of Pol δ in replication of the leading strand is uncertain. In this work, we use a reporter system in Saccharomyces cerevisiae to measure mutation rates at specific base pairs in order to determine the effect of heterozygous or homozygous proofreading-defective mutants of either Pol ε or Pol δ in dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 123 publications
2
47
1
Order By: Relevance
“…Most previous experimental studies confirm the classical model, including experiments with mutant polymerases (Pursell et al 2007;Kunkel and Burgers 2008;Nick McElhinny et al 2008;Johnson et al 2015) or incorporation of ribonucleotides Clausen et al 2015;Johnson et al 2015), where specific mutations were observed on the corresponding strands; experiments investigating the association of proteins with leading and lagging strands of DNA replication forks (Yu et al 2014); and biochemical experiments of assembly and stabilization of replication complexes (Georgescu et al , 2015Langston et al 2014). Moreover, recent evidence suggests that Pol epsilon does not proofread errors made by Pol delta (Flood et al 2015). This model (Johnson et al 2015) also contradicts our data, as it does not predict the opposite strand biases we observe in cancers with mutated Pol epsilon and Pol delta (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Most previous experimental studies confirm the classical model, including experiments with mutant polymerases (Pursell et al 2007;Kunkel and Burgers 2008;Nick McElhinny et al 2008;Johnson et al 2015) or incorporation of ribonucleotides Clausen et al 2015;Johnson et al 2015), where specific mutations were observed on the corresponding strands; experiments investigating the association of proteins with leading and lagging strands of DNA replication forks (Yu et al 2014); and biochemical experiments of assembly and stabilization of replication complexes (Georgescu et al , 2015Langston et al 2014). Moreover, recent evidence suggests that Pol epsilon does not proofread errors made by Pol delta (Flood et al 2015). This model (Johnson et al 2015) also contradicts our data, as it does not predict the opposite strand biases we observe in cancers with mutated Pol epsilon and Pol delta (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Given evidence that the exonuclease activity of Pol δ, but not that of Pol ε, proofreads errors made by Pol α[12], and evidence that Pol δcan also proofread errors made by Pol ε [13], the higher mutation rate in the pol3-exo - msh6 Δ strain could be due to loss Pol δ proofreading of errors made by any of the three replicases, whereas loss Pol ε may only proofread its own errors. The different mutation rates in the pol3-exo - msh6 Δ and pol2-exo - msh6 Δ strains could also be related to differences in activation of the S phase checkpoint in proofreading-deficient strains (see [26] and references therein).…”
Section: Resultsmentioning
confidence: 99%
“…Thus it is possible that in the absence of only one of the two proofreading activities intrinsic to Pol ε and Pol δ, the exonuclease that remains intact in one replicase can proofread mismatches generated by the other major, but proofreading-deficient replicase [2,12]. Indeed, a recent study [13] provides evidence that Pol δ proofreads errors made by Pol ε. Theoretically, extrinsic proofreading may also be catalyzed by other 3′-exonucleases (e.g., see [52]). To the extent that extrinsic proofreading may occur during replication in yeast, this implies that (i) the actual base selectivity of the replicases in vivo could be substantially lower than calculated here, and therefore more in line with the estimates from studies in vitro , and (ii) the base selectivity calculated here for lagging strand replication may be a mixture of the base selectivity of Pol α plus Pol ε, because both polymerases contribute to the mature lagging strand (see [21,53], and more recently [5,8]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polε exonuclease deficiency results in a very small increase in the mutation rate in both yeast and human cells [8,83,84], even though the fidelity of purified Polε in vitro is strongly affected by the inactivation of proofreading [85,86]. It has been suggested that the majority of Polε errors are corrected in cells by extrinsic mechanisms, for example, by the exonuclease activity of Polδ [2,87]. On the other hand, many Polε exonuclease domain mutations found in cancers, and particularly P286R, were predicted to affect DNA binding [23,24,63].…”
Section: Mechanisms Of the Ultramutator Phenotypementioning
confidence: 99%